Comparisons Between Transparency In The United States of America(US) Corporate Bond Market and European Corporate Bond Market: Criticisms of Transparency In US Markets From European Markets Perspective - Zainudin, WNRA; Board, J (Int Business Information Management Assoc-Ibima, 2024)
This paper investigates the differences between the impacts of transparency in the US and European Corporate Bond Markets by studying the criticisms of transparency in the US markets from European markets perspective. The study makes two assumptions namely as the level of understanding on transparency in the European market increase; the spreads decrease and the volume of trading do not decrease. Then the study construct a regression on the data sets on all of subset of the European market selected that consists of the average best bid-ask spread (presented in proportional spread) and the number of trading volumes. The results from methodology are giving favorable results or advantages of implementation of transparency that is consistent with the phenomenon experienced by US corporate bond markets. Thus, it can be concluded that it would be optimal to introduce transparency in the markets but with some limited post-trade transparency.